2010
DOI: 10.1128/mcb.01292-09
|View full text |Cite
|
Sign up to set email alerts
|

Sti1 Regulation of Hsp70 and Hsp90 Is Critical for Curing of Saccharomyces cerevisiae [PSI+] Prions by Hsp104

Abstract: Although propagation ofor Hsp90 interaction cured less efficiently, and the Hsp90 inhibitor radicicol abolished curing, implying that Sti1 acts in curing through Hsp70 and Hsp90 interactions. Accordingly, strains lacking constitutive or inducible Hsp90 isoforms cured at reduced rates. We confirm an earlier finding that elevating free ubiquitin levels enhances curing, but it did not overcome inhibition of curing caused by Hsp90 defects, suggesting that Hsp90 machinery is important for the contribution of ubiqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
85
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(90 citation statements)
references
References 73 publications
5
85
0
Order By: Relevance
“…These findings are consistent with our previous work, suggesting that Ssa1-21p antagonizes prions by a mechanism similar to that of overexpressing Hsp104 (Hung and Masison 2006;Reidy and Masison 2010) and point to Sis1p as a specific Hsp40 involved in this mechanism. We also showed previously that depleting Ydj1p, the other major cytosolic Hsp40, enhances the anti-[PSI 1 ] effects of Ssa1-21p (Jones and Masison 2003), which suggests that Ydj1p interferes with the prion impairment caused by Ssa1-21p.…”
Section: [Psi 1 ] Is Lethal To Cells Expressing Hdj1p In Place Of Sis1psupporting
confidence: 82%
See 2 more Smart Citations
“…These findings are consistent with our previous work, suggesting that Ssa1-21p antagonizes prions by a mechanism similar to that of overexpressing Hsp104 (Hung and Masison 2006;Reidy and Masison 2010) and point to Sis1p as a specific Hsp40 involved in this mechanism. We also showed previously that depleting Ydj1p, the other major cytosolic Hsp40, enhances the anti-[PSI 1 ] effects of Ssa1-21p (Jones and Masison 2003), which suggests that Ydj1p interferes with the prion impairment caused by Ssa1-21p.…”
Section: [Psi 1 ] Is Lethal To Cells Expressing Hdj1p In Place Of Sis1psupporting
confidence: 82%
“…Curing was done as described (Reidy and Masison 2010). Briefly, cells carrying pMR26L, which encodes copper-inducible Figure 1) in wild-type (SSA1) and SSA1-21 strains that have a deletion of chromosomal SIS1 and carry a wild-type SIS1 gene on a single-copy URA3 plasmid to ensure viability.…”
Section: Curing Cells Of [Psi 1 ] By Hsp104 Overexpressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we found that 115-7c prolonged the association of both Hsp70 and Hsp90 with Q103. It is not yet clear why Hsp70 and Hsp90 are co-incident in their accumulation because we did not directly detect the co-chaperone, Sti1, which normally links these chaperones (27,29). However, it is possible that the stringency of the washing steps removed this factor or that it is present at low levels.…”
Section: Discussionmentioning
confidence: 65%
“…For example, Hsp70 activity appears to be required to facilitate Hsp104 disaggregase activity during the propagation and inheritance of prions (22)(23)(24) and other model substrates (25). In addition, Hsp26 works with Hsp104 to help break large fibrils into inheritable fragments (26), while Hsp70 and Hsp90 also assist in this process (27). Some of these shared activities may involve direct interactions between chaperones; for example, Hsp70 binds directly to Hsp104 (28) and Hsp70 and Hsp90 can be physically linked via Sti1 (29).…”
mentioning
confidence: 99%